STING Contributes to Host Defense Against Staphylococcus aureus Pneumonia Through Suppressing Necroptosis - Liu, Zhen-Zhen; Yang, Yong-Jun; Zhou, Cheng-Kai; Yan, Shi-Qing; Ma, Ke; Gao, Yu; Chen, Wei (Frontiers in Immunology, 2021)
STING (Stimulator of interferon genes) is known as an important adaptor protein or direct sensor in the detection of nucleotide originating from pathogens or the host. The implication of STING during pulmonary microbial infection remains unknown to date. Herein, we showed that STING protected against pulmonary S.aureus infec-tion. STING deficiency resulted in increased mortality, more bacteria burden in BALF and lungs, severe destruction of lung architecture, and elevated inflammatory cells infiltration and inflammatory cytokines secretion. Meanwhile, STING defi-ciency promoted early pulmonary colonization of S.aureus before developing exces-sive inflammation. TUNEL staining and LDH release assays showed that STING-/- mice had increased cell death than WT mice. Our in vivo and in vitro findings further demonstrated this cell death as necroptosis. Importantly, blocking necroptosis activa-tion rescued host defense defect against S.aureus pneumonia in STING-/- mice. Hence, these results reveal an important role of STING in suppressing necroptosis activation to facilitate early pathogen control during pulmonary S.aureus infection.